Out-of-class English Language Learning and Use among Post-Secondary Malaysian Students - Ishak, Nurhamizah (International Journal of Language Education, 2025)
Out-of-class learning is an additional vital component in successful English language acquisition among proficient ESL users. Thus, this study employed a quantitative research approach to investigate out-of-class English language practice by Malaysian ESL post-secondary students. 106 first-semester Diploma in Tourism Management students at a Malaysian university were the respondents of this study. The respondents were asked to fill in a survey questionnaire about their Malaysian Certificate of Education (SPM) English grade, perceived ability of four language skills (reading, writing, listening, speaking) and vocabulary knowledge in English language, frequency of using the four skills during their free time, and types of vocabulary learning approach they applied. The data was later statistically analysed using frequency, percentage, mean, standard deviation, one-way ANOVA, and simple linear regression tests. Out of the four language skills, the respondents reported they frequently practiced or applied listening skill in the English language the most during their free time, whereas writing is the least used or applied skill. With regards to their self-perceived language skills, most respondents claimed that they have good mastery of reading skill, but writing skill is their Achilles heel. In addition, this study found the respondents’ English language proficiency level (SPM English grade) and perceived language skills influence their frequency of practicing or applying each language skill during their free time. Finally, in terms of their vocabulary learning approach, most respondents said they do not actively try to increase their vocabulary knowledge during their free time. Nevertheless, they tend to unintentionally discover and learn new English words while doing everyday activities.